THE IMPORTANT ROLE OF TEACHERS IN INCREASING STUDENT MOTIVATION POST COVID-19 PANDEMIC - Sulaiman, Baso; Kuddus, Muhammad; Pasolang, Yoseph (PT. BATARI EDU CALYA, 2023)
This research aims to know and explain the importance of the role of teachers in increasing student motivation in the post-COVID-19 pandemic. This is done to see the extent of the teacher's role in providing support and guidance to students after the transition period of online learning methods to learning methods like before, namely face-to-face. This study used qualitative research with data collection methods through observation and interviews with teachers in 13 high school / equivalent schools in Palopo City. The data analysis technique uses the interactive data analysis technique of Miles and Hubberman's theory with 4 stages of the analysis process, namely data collection, data reduction, data presentation, and drawing conclusions. The research results obtained from this research are that the important role of teachers in increasing students' learning motivation after the Covid-19 pandemic is very necessary to increase students' interest in learning. Interest in learning that grows well will certainly affect the achievements that will be produced by students at school. So it is very clear that a professional teacher will play a role as a motivator to improve the academic achievement of students where teachers teach and educate.